Systematic review of forensic entomology and a meta-analysis of the effect of the presence of chemicals in carcasses - Carolina Alvim Munaier (2019)
Despite being considered a relatively recent science, it is already possible to find a vast literature on Forensic Entomology, and an extensive quantity of informations about it. With it, arises a need to gather and synthesize these informations, in order to organize and integrate the knowledge. It is in this scenario that systematic reviews and meta-analyzes are inserted, once they are extremely essential tools in perform this synthesis. Therefore, we reviewed the current global state of Forensic Entomology and we performed a meta-analysis of the effect of the presence of chemical substances on insect parameters of the Forensic Entomofauna. We pulled data from 309 articles for the systematic review, and among those, 24 articles composed the meta-analysis. Articles about this science have been found in 33 countries, suggesting that Forensic Entomology needs to develop even more, to consolidate its global status. Studies of survey, insect successional and that focus on the Diptera order were the most abundant. Overall, the presence of chemical substances in carcasses had positive effect on insect development time, insect colonization, insect length and insect width, and had negative effect on insect survival and insect performance. The effects of the presence of chemical substances vary according to the type of substance and the type of the carcass containing the substance, due to its individual characteristics